Women’s mental health in the doctoral context: Protective function of the psychological capital and academic motivation - Angel Deroncele-Acosta; Roger Pedro Norabuena-Figueroa; Emerson Damian Norabuena-Figueroa (Women's Health)
Background: Science recognizes the anxieties, depression, stress, and “turbulences” that women face in doctoral studies, but women’s mental health in this context is still little addressed, even though it is a critical aspect for the well-being, persistence, and success of women doctoral candidates, who continue to be underrepresented in many professional fields. Objectives: The study aims to evaluate the relationship between academic motivation, psychological capital, and university academic performance (UAP) and to identify factors of female mental health success. Design: A cross-sectional, mixed-methods study was conducted with a sample of 108 female doctoral students from a university in Lima, during the first quarter of 2024. Methods: In the quantitative phase, three standardized scales were administered to assess academic motivation, psychological capital, and university academic performance (UAP). In the qualitative phase, interviews were conducted to gather relevant information on mental health. Results: The findings emphasize five important points: (1) levels and the relationship between psychological capital, academic motivation, and performance, (2) motivational behavior according to study cycles, (3) risk and protection profiles, (4) protective functions, and (5) mental health success factors. The results indicate that 36% of the women have a low level of psychological capital, 34% have a medium level of academic motivation, and 37% have a high level of UAP, likewise “Intrinsic Motivation toward Accomplishment” is the positive core where most of these women converge. Significant differences were found between the study cycles with academic motivation and “University Academic Performance,” and a significant gap between these variables. The risk profile (which limits performance) and the protective profile which allows high performance are determined; this positive profile is identified by women who present a high level of “Self-efficacy.” The study demonstrates that “Psychological Capital” and “Academic Motivation” along with the dimensions of “Self-efficacy” and “Intrinsic Motivation to Experience Stimulation” serve protective functions. Fourteen success factors for women’s mental health were identified and organized into four main approaches: Optimism, Hope, Resilience, and Self-efficacy. Conclusion: Limitations and future projections are discussed. The practical implications include implementing psychological support programs, fostering intrinsic motivation, integrating psychological assessments, establishing support networks, and making tailored curricular adjustments.